Dry needling curricula in entry-level education programs in the United States for physical therapists. (4th March 2021) - Matthews, Lynn; Ford, Greg; Schenk, Ron; Ross, Michael; Donnelly, Joseph
ABSTRACT: Objectives:  The objective of this paper was to determine the extent to which dry needling is instructed in entry-level education programs for physical therapists. Methods:  Program directors from 226 entry-level education programs recognized by the Commission on Accreditation in Physical Therapy Education were recruited via e-mail to participate in an anonymous 35-item electronic survey during the 2017-2018 academic year.  The survey evaluated dry needling curricula, faculty qualifications, attitudes and experience, and programs' future plans for teaching dry needling. Results:  A total of 75 programs responded to the survey (response rate = 33.1%).  Forty (53.3%) had integrated dry needling theory and psychomotor training into their programs and 8 (10.6%) planned to include such content in their curriculum in the future.  Of the 40 respondents, 28 indicated that dry needling education was integrated into a required course, 4 indicated that dry needling was an elective course, and 8 did not specify how dry needling education was integrated. Faculty teaching dry needling appear to be well qualified, with the majority having 5-10 years of experience using dry needling in clinical practice. The primary reason for programs not teaching dry needling is that it was not considered an entry-level skill. Discussion:  There appeared to be variability in how dry needling was integrated into the curricula, as well as in the depth and breadth of instruction.  Our research may serve as a baseline for faculty to assess existing dry needling curricula and as a guide for developing curricula in new or existing physical therapy programs.